OP0223 Inhibition of Casein Kinase-2 Alleviates the Profibrotic Effects of Transforming Growth Factor Β in Systemic Sclerosis. (23rd January 2014) - Zhang, Y.; Dees, C.; Beyer, C.; Lin, N.-Y.; Distler, O.; Schett, G.; Distler, J.
Abstract : Background: Casein kinase-2 (CK2)is a ubiquitous, highly conserved serine/threonine kinase. CK2 presents as a tetramer composed of 2 catalytic subunits (α orα') and 2β regulatory subunits, whichareessential for cell viability. Meanwhile, JAK-STAT signaling is involved in the regulation of cell survival, proliferation, and differentiation. Recently, we have shown thattargeting of JAK2 might be an interesting molecular approach for the treatment of systemic sclerosis (SSc). However, the role of CK2 in SSc and the functional relationship between CK2 and JAK-STAT signaling in SSc have not been established. Objectives: The purpose of the study was to characterize whether CK2 contributes to the pathologic activation of fibroblasts in patients with SSc, to evaluate the anti-fibrotic potential of CK2 inhibition for the treatment of SSc, and to investigate the CK2-JAK2-STAT3 signaling interactions in fibrosis. Methods: Activation of CK2, JAK2, and STAT3 in human skin and in experimental fibrosis were determined by immunohistochemical analysis. CK2 signaling was inhibited by the selective CK2 inhibitor 4, 5, 6, 7-Tetrabromobenzotriazole (TBB). The mouse models of bleomycin-induced and TGF-β receptor I (TBR)-induced dermal fibrosis were used to evaluate the anti-fibrotic potential of specific CK2 inhibition in vivo . Results: Increased expression of CK2 was detected by immunohistochemistry in skin sections of SSc patients, particularly in fibroblasts. Inhibition of CK2 by TBB in cultured fibroblasts completely abrogated the stimulatory effects of TGFβ on collagen release (p<0.05). After TBB treatment, stress fiber formation and α-smooth muscle actin (α-SMA) expression in TGFβ-stimulated fibroblasts were significantly reduced by 97% (p=0.0064) and 69% (p=0.0280). Besides reduced fibroblast activation, western blot analyses showed almost complete normalization of phosphorylated JAK2 (pJAK2) levels in the cytoplasm and of phosphorylated STAT3 (pSTAT3) levels in the nucleus of TGFβ-treated fibroblasts upon pre-incubation with TBB (p=0.0004 and p=0.0214). In addition, treatment with TBB effectively prevented bleomycin-induced fibrosis in mice with decreased dermal thickness by up to 70% (p<0.0001) and efficient reductions in myofibroblast counts by up to 68% (p=0.0002). TBR-induced fibrosis in mice was strongly ameliorated by TBB with efficient reductions of dermal thickening by 75% (p<0.0001). Myofibroblast counts and hydroxyproline content also decreased by 59% and 40% (p<0.0001 and p=0.0193), respectively. In both murine models, we observed reduced pJAK2 and pSTAT3 expression as analyzed by immunohistochemistry. Conclusions: We demonstrate that CK2 is activated in SSc and prove that inhibition of CK2 reduces canonical TGF-β signaling and prevents experimental fibrosis in different preclinical models. Considering the potent anti-fibrotic effects of CK2 inhibition, our study might have direct translational implications. These data provide first evidence that targeting CK2 may be a novel therapeutic approach for fibrotic diseases. Disclosure of Interest: None Declared